The Making and Unmaking of a Megaproject: Contesting Temporalities along the LAPSSET Corridor in Kenya. Issue 5 (1st March 2021) - Aalders, Johannes Theodor; Bachmann, Jan; Knutsson, Per; Musembi Kilaka, Benard
Abstract: In this paper, we show how communities in Northern Kenya proactively engage an unfolding megaproject and the temporalities it evokes—the Lamu Port South Sudan Ethiopia Transport Corridor (LAPSSET). We argue that the latitude communities have in contending with megaprojects is broader and more dynamic than passive reception of or outright resistance against the futures promised. By introducing the concepts of entangling and fraying, we emphasise the agency communities create for themselves by appreciating their strategies and expressions of stabilising or troubling the "megaproject". While entangling refers to practices through which communities attach additional features to an otherwise rather stable vision of its "meganess", fraying, in contrast, describes the strands that splice off towards different spatio‐temporal imaginaries. We discuss these practices in four instances of engaging LAPSSET: constructing temporary homes at project sites; engaging in land reform; disputing land acquisition at oil exploration sites; and contesting a planned resort city. Muhtasari: Kwenye jarida hili, tunaonyesha jinsi jamii kaskazini mwa Kenya wanajihusisha na mradi wa muundo msingi unaojulikana kama Lamu Port South Sudan Ethiopia Transport Corridor (LAPSSET). Tunaonesha kuwa uhusiano kati ya jamii na miradi ya miundo msingi ufanyika kwa njia mingi na sio tu ati hao huikubali ama huipinga. Tukitumia dhana mbili amabazo ni kujihusisha na kukabiliana tunaonyesha jinsi jamii huwa na ushawishi mkubwa na uwezo wa kutumia mbinu tofauti ambazo zinaweza kustahimilisha ama kuvuruga mradi huo. Katika dhana ya kujihusisha, tunaangazia jinsi jamiii huambatanisha matakwa yao na mipango maalum ambayo hutarajiwa kutoka kwa miradi "kubwa" ya miundo msingi. Dhana ya kukabiliana nayo inaashiria maoni tofauti ambazo haziambatani na fikira za wapangaji wa miradi. Tunafanya hivi kwa kuzungumzia matukio nne ambayo jamii wanajihusisha na mradi wa LAPSSET. Matukio haya ni ujenzi wa makaazi yanayodumu kwa muda mfupi kwenye maeneo ya mradi; mikakati ya jamii kusajili ardhi yao; pingamizi za ardhi kuchukulia kwa miradi ya mafuta; na pingamizi juu ya mipango ya ujezi wa mji mpya wa mapumziko.